Learning Analytics dalam Pembelajaran Digital: Kajian Konseptual tentang Peluang, Tantangan, dan Arah Implementasi - Annisa Putri (Suria Academic Press, 2026)
The rapid growth of digital learning environments has generated large volumes of learner data from various online learning activities. This development has accelerated the adoption of Learning Analytics as a data-driven approach to support more informed and evidence-based pedagogical decision-making. Despite its increasing implementation across educational settings, Learning Analytics continues to face significant challenges related to technology, ethics, data governance, and human resource readiness. This article aims to provide a conceptual analysis of the opportunities, challenges, and future directions of Learning Analytics implementation in digital learning. The study employs a conceptual research approach by critically analyzing and synthesizing theories and previous scholarly works relevant to Learning Analytics. The analysis involves identifying key concepts, organizing major themes, comparing different perspectives, and developing an integrated conceptual framework. The findings indicate that Learning Analytics plays a strategic role in promoting personalized learning, adaptive learning, early warning systems, continuous assessment, and evidence-based educational decision-making. However, its implementation is constrained by issues such as data privacy, information security, algorithmic bias, educators' data literacy, technological infrastructure, and institutional governance. As a conceptual contribution, this article proposes an implementation framework that integrates learning data sources, analytical processes, pedagogical decision-making, and ethical data governance to support adaptive, sustainable, and learner-centered digital education.